La post-fantasy: il ciclo letterario Inquisitore Eymerich di Valerio Evangelisti come una realizzazione dell’elemento fantastico tramite la narrazione postmoderna - Przełucka, Patrycja (Romanica Silesiana, 2020)
This article examines the literary series of Inquisitore Eymerich by Valerio Evangelisti, a variegated macronarrative, which, resisting generic classification, introduces innovation to the panorama of contemporary Italian fantasy. Departing from the analysis of the salient features of the series such as intertextuality, hybridization, storiographic metafiction, and transfictionality, the article examines closely the areas of postmodern narration and inquires into the role of the fantastic element in Italian literature. Evangelisti makes the most of postmodern narrative strategies and of fantasy’s ability to penetrate various media in order to provide a tool of critical reflection on human history with an emphasis on the phenomenology of power. By interweaving different literary genres and inviting readers to produce their own interpretations in form of fan fiction, Evangelisti creates a new type of committed narrative, post-fantasy, which presents a new conception of postmodern narrative, one that overcomes the barrier between the literary fiction and the genre fiction.